Fear of COVID-19 and related factors affecting mothers’ breastfeeding self-efficacy during the pandemic - Ergün, Sibel; Kaynak, Serap; Aydın, Beray (Revista da Escola de Enfermagem da USP, 2022)
Objective: This study aimed to determine the breastfeeding self-efficacy levels of mothers during the pandemic period, to compare them according to various characteristics, and to examine the relationship between the fear of COVID-19 and breastfeeding self-efficacy. Method: The data of this descriptive and cross-sectional were collected through a web-based survey of 392 mothers between June and August 2021. The data collection tools were the Introductory Data Form, the Breast-feeding Self-Efficacy Scale-Short Form, and the Fear of COVID-19 Scale. Results: The mean score for breastfeeding self-efficacy was found to be 56.18 ± 8.24, while the mean score for the Fear of COVID-19 scale was 21.77 ± 6.14. Having a high fear of COVID-19, breastfeeding more frequently in this period, and suspecting that they had COVID-19 affected the breastfeeding self-efficacy scores positively, whereas graduating from primary school had a negative effect on self-efficacy. Conclusion: The breastfeeding self-efficacy of mothers who were fearful of COVID-19, who breastfed more frequently during the pandemic, and who had a higher education level were positively affected.